Mediating Digital Narratives: Parental Roles in Enhancing Multimodal Literacy for Early Childhood - Isna Maylani; Farah Rizkita Putri; Ayu Kamilatun Nihlah (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2026)
This study explores how parental mediation in digital children’s literature enhances multimodal literacy in early childhood. It analyzes the experiences of eight mothers of children aged 5–6 years, gathered through asynchronous written interviews and examined using thematic analysis. The findings demonstrate that multimodal features of digital narratives, such as visuals, audio, and interactive elements, stimulate vocabulary growth, narrative comprehension, and creative expression. Crucially, these outcomes are strengthened when parents actively co-read, guide discussions, and critically select appropriate content. The study highlights that digital literature extends beyond entertainment to become a pedagogical tool for literacy development when mediated effectively. It further underscores the need to integrate digital narratives into early childhood education, aligning them with contemporary pedagogical strategies emphasizing parental involvement, multimodal engagement, and balanced screen-time management.